(untitled) (Archive of Conferences, 2020)
The article analyzes the importance of words expressing movement in the work of Shavkat Rahmon in the formation of metaphors, with the help of examples of ways to use language tools more effectively. The poet’s work is based on the ability of words to express metaphor.